Effectiveness of Electronic Contracts in Civil Law: Project Management - Barrero, Julián Darío; Herrera, Farid Nazzar; Ojeda, Jonathan Karlo Martinez (Journal of Ecohumanism, 2024)
Digitalization has profoundly transformed legal relationships, and electronic contracts have established themselves as a key tool in contemporary contracting. This study analyzes the legal effectiveness of electronic contracts in the field of civil law, with special emphasis on the regulatory, technological, and practical challenges faced by parties when formalizing agreements in digital environments. Through a documentary review and comparative analysis of recent international regulations and doctrines, opportunities that strengthen legal certainty are identified, as well as gaps that require regulatory attention. The results suggest that, although there are significant regulatory advances, challenges remain around authenticity, informed consent and proof of contract.